Answer:
(x, y) = (11/7, 2/7)
Step-by-step explanation:
You want the solution to the system of equations ...
We notice the x-coefficients have the ratio 1:2. This means we can eliminate the x-variable by subtracting the second equation from 2 times the first:
2(4x -y) -(8x -9y) = 2(6) -(10)
8x -2y -8x +9y = 12 -10 . . . . . . . eliminate parentheses
7y = 2 . . . . . . . . . . . . . . . . collect terms
y = 2/7 . . . . . . . . . . . . divide by 7
Substituting into the first equation gives ...
4x -2/7 = 6
4x = 6 2/7 = 44/7 . . . . . add 2/7
x = 11/7 . . . . . . . . . . . divide by 4
The solution is (x, y) = (11/7, 2/7).